Fenomena Black Swan: Dampak Covid-19 Terhadap Herding Behavior Pada Sembilan Sektor di Pasar Modal Indonesia: Black Swan Phenomenon: The Impact of Covid-19 On Herding Behavior in Nine Sectors in The Indonesian Stock Market - Harahap, Serarifi Elagin; Achsani, Noer Azam; Sasongko, Hendro (Jurnal Aplikasi Bisnis dan Manajemen, 2023)
This study examines herding behavior in Indonesian capital market during COVID-19 pandemic. We assume, COVID-19 announcement has a black swan effect on the Indonesian capital market, which results in behavioral anomalies such as herding behavior. Herding can cause high volatility and market destabilization. This research used Cross-Sectional Absolute Deviation (CSAD) method to determine herding behavior in nine sectors (225 companies) on the Indonesia Stock Exchange (IDX) caused by black swan effect of the COVID-19 pandemic. The samples were stocks in nine sectors in IDX, consisting of 225 companies. The observation period is from February 01, 2018, to March 31, 2022. The study found that JKBIND (basic industry and chemicals) is the only sector that tends to herd. Meanwhile, there was no tendency for herding to occur in the other eight sectors. This study found that Indonesian capital market is quite rational because it is stable during the COVID-19 period (only one sector has a herding behavior trend). Herding behavior is an interesting topic during crisis periods, when investors share their fears and are vulnerable to large-scale financial panics. This research can increase the understanding of the capital market and the financial impact of the COVID-19 pandemic for investors and regulators. Keywords: COVID-19, Cross-Sectional Absolute Deviation (CSAD), herding behavior, Indonesia, stock market